The Potential of Agriculture in Science Teaching - Amos Dreyfus (Journal of Research in Rural Education, 1986)
While the role of science in agricultural education is fairly well understood, the potential role of agriculture in science teaching seems to have been, so far, a neglected issue. The educational potential of agriculture stems from the diversity of its components and on the tangibility of some of these components. The web of intellectual and practical activities which is called agriculture embraces most of the elements of modern science teaching. whichever orientation this teaching may wish to adopt: enquiry-experimental or socio-technological. As a science based human activity. it may provide the educator with a unique combination of educational opportunities, in a context which is authentic and accessible to the pupil and to the teacher.